Evaluation of Database Replication Techniques for Cloud Systems - Santana, Melissa; Armendáriz-Iñigo, José Enrique; Muñoz-Escoí, Francesc D. (Computing and Informatics, 2016)
Cloud computing is becoming one of the preferred paradigms to deploy highly available and scalable systems. These systems usually demand the management of huge amounts of data, which cannot be solved with traditional database systems. Traditional replication protocols are not scalable enough for a cloud environment. This paper evolves different static replication techniques to achieve transactional support providing high availability and scalability as needed in cloud systems. This proposal offers different consistency levels according to the demands of client applications using a replication strategy based on a combination of traditional replication techniques with asynchronous epidemic updates. We have run several simulations that show this is an interesting approach to provide transactional support to clients with different consistency guaranties while leveraging the resources used.